Critical-wedge theory and the Mesozoic accretionary wedge of New Zealand. (May 2019) - Ring, Uwe; Mortimer, Nick; Deckert, Hagen
Abstract: We apply principles of critical-wedge theory to explain the Jurassic and Early Cretaceous tectonic development of the Mesozoic accretionary wedge of New Zealand, one of the best-exposed subduction complexes on Earth, by summarizing factors that can lead to drastic changes in wedge balance. The wedge has a Carboniferous to Cretaceous (∼330-110 Ma) stratigraphic record, with an early Cretaceous (∼145-130 Ma) hiatus in clastic deposition across the Esk Head Melange near the front of the wedge. In the rear of the wedge, the age of moderately high-pressure metamorphism of the Otago Schist, which represents the forearc-high of the wedge, occurred near the end of this stratigraphic hiatus. The Otago Schist has a subhorizontal foliation indicative of underplating as the mode of accretion. The outer (frontal) part of the wedge has a subvertical foliation indicative of frontal accretion. We propose that in the Jurassic and earliest Cretaceous the wedge grew by frontal accretion. By ∼135 Ma the wedge became too long and was subcritical. This resulted in tectonic erosion of the front of the wedge. The tectonically eroded material was underthrust/underplated beneath the rear of the wedge to form the subhorizontally foliated Otago Schist. Colliding seamounts and/or oceanic plateaux (preserved in the Esk Head Melange) may have aided wedge instability. The proposed wedge instability and increased horizontal shortening was largely coeval with major changes in the chemistry of subduction-related arc magmatism and a phase of shortening and high-pressure metamorphism in the arc. Our model provides a holistic and coherent interpretation explaining the major tectonic features of the long-lived New Zealand part of the east Gondwana subduction zone. Highlights: Synthesis of the Jurassic to mid Cretaceous tectonic development of the Torlesse accretionary wedge in New Zealand, which is one of the best-exposed subduction complexes on Earth. Novel approach links a stratigraphic gap at the front of an accretionary wedge with, and actually considers it as the driver for, high-pressure metamorphism in the rear of a wedge. Proposed model provides a holistic and coherent interpretation explaining the major tectonic features of the long-lived New Zealand part of the east Gondwana subduction zone.